Analysis of Culinary Experience Development Strategies to Enhance Restaurant Brand Value in Bali - Unggul Putra Jaya (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2025)
In recent years, the culinary landscape in Bali has evolved far beyond the simple act of serving food. As the island continues to draw visitors seeking authentic and memorable experiences, restaurants are faced with a new challenge: creating culinary encounters that not only satisfy the palate but also engage the senses, evoke emotion, and shape the identity of a brand. Travelers today often arrive with expectations that stretch beyond taste—they look for atmosphere, cultural expression, meaningful interactions with staff, and visually compelling dishes that capture the essence of the place. This shift in consumer behavior highlights the growing importance of understanding how a holistic culinary experience can contribute to brand value. Yet, despite the prominence of gastronomic tourism in Bali, empirical research that examines the influence of four key dimensions—sensory experience, emotional experience, service interaction, and food presentation—on restaurant brand value remains limited. This study employs a quantitative approach using purposive sampling to gather responses from 150 individuals who had dined at restaurants in Canggu, Ubud, Kuta, and Seminyak. Multiple regression analysis was conducted to determine the contribution of each dimension of the culinary experience to brand value. The findings reveal that all four dimensions exert a positive and significant influence, with food presentation emerging as the strongest predictor. These results illustrate that culinary experience is not a peripheral element but a central component in shaping a restaurant’s brand identity. When thoughtfully curated—from the aesthetics of the dishes to the emotional tone of service interactions—culinary experiences enhance perceived quality, strengthen brand recognition, and foster long-term consumer loyalty. The study provides both conceptual insight and practical guidance for hospitality practitioners in Bali, emphasizing the role of culinary experience as a strategic pillar in developing and sustaining brand value within a highly competitive tourism environment.